Determinants of Employee Performance in Supervised Schools in Ulubongka District, Tojo Una-Una Regency - Misna Tansidi; Moh Rolli Paramata; Hasanuddin Hasanuddin (International Journal Of Education, Social Studies, And Management (IJESSM), 2026)
This study aims to analyze the influence of compensation, work motivation, work environment, and job satisfaction on employee performance in supervised schools in Ulubongka District, Tojo Una-Una Regency. The study employed a quantitative research method, with data collected through questionnaires, interviews, observations, and documentation. Data analysis was conducted using multiple linear regression analysis. The results indicate that compensation, work motivation, work environment, and job satisfaction have a positive and significant effect on employee performance. Work motivation was identified as the most dominant variable in improving employee performance. Simultaneously, all independent variables exerted a significant influence on employee performance. Therefore, improving employee performance can be achieved through better compensation, enhanced work motivation, the creation of a conducive work environment, and increased employee job satisfaction.